Sustainable urban landscapes: making the case for the development of an improved management system - Mohd. Tahir, Osman; Roe, Maggie H. (Faculty of Design & Architecture, Universiti Putra Malaysia, 2006)
In order to achieve high quality urban landscapes it is essential to engage an appropriate management system. Such a system needs to be flexible enough to allow consideration of both urban change and the changing needs and demands of landscape users. Based on an investigation of the literature, this paper makes the case for the development of an effective management system and concludes that changes in urban landscape management have not kept up with urban expansion. Moreover as the trend in the objectives for urban development in Malaysia and around the world is towards achieving more sustainable development, the paper highlights the importance of establishing more appropriate landscape management systems as fundamental to the achievement of sustainability objectives